AUTOIMMUNE GASTRITIS AND GASTRITIS ASSOCIATED WITH CELIAC DISEASE - Qobiljonova Shaxnoza Rustam qizi; Tolipova Azizahon Farxod qizi (Innovate Conferences, 2025)
Celiac disease is one of the most common autoimmune diseases in the world, affecting approximately 1% of the population. The typical form is manifested by malabsorption syndrome ; in childhood, the disease leads to disturbances of physical, psychomotor and sexual development. Celiac disease has been actively studied for 120 years, but only in the last decade have significant results been achieved that have changed the view of this disease. It was found that celiac disease is a systemic autoimmune disease affecting not only the small intestine, but also the organs of the endocrine and digestive systems. At the same time, the mechanisms of development of associated autoimmune diseases in celiac disease remain insufficiently understood. Thus, the study of changes in other organs and systems of the body in celiac disease is a priority today. In recent years, interest has increased in studying the involvement of the stomach in the pathological process in celiac disease. Based on morphological data, it was found that the prevalence of chronic gastritis (CG) in individuals with celiac disease is 80%-97.8%. The most studied type of chronic gastritis in celiac disease is lymphocytic . At the same time, other forms of chronic gastritis in celiac disease have been studied less. Morphological descriptions of chronic gastritis in celiac disease are quite contradictory. Thus, in lymphocytic gastritis in children with celiac disease, the antral part of the gastric mucosa (GM) is most often described as affected . Some researchers find that in other forms of chronic gastritis against the background of celiac disease, the fundus of the stomach is affected. In isolated studies, a relationship between celiac disease and autoimmune gastritis is traced. Thus, the etiological structure, clinical, functional, morphological, and other features of chronic gastritis in celiac disease still remain unclear. The prevalence, etiology, and pathogenesis of autoimmune gastritis in celiac disease are unknown. The question of the effect of a gluten-free diet (GFD) on the gastric mucosa remains open.